TEACHING VOCABULARY BY USING PUZZLE GAMES TO YOUNG CHILDREN AT POINT EDUCATION CENTER, LAWEYAN, SURAKARTA - Baehaqi, Muski (2007)
This study is aimed at describing the implementation of teaching vocabulary by using puzzle games, the problem faced by the teachers and the students, and the student's response on the implementation of puzzle games in teaching vocabulary. The result of this study is expected to contribute the teaching learning English at the course particularly in vocabulary skill. The observation was done in Point Education Center, Surakarta. The writer observed the young learners as the subject of research. The object of research was the implementation of teaching vocabulary by using puzzle games. Here, the writer only observed and described the implementation of puzzle games in teaching vocabulary. Then he described the problem faced by the teacher and the students, and the student's response on implementation of puzzle games in teaching vocabulary. The writer has interviewed all teachers and 4 students to give their comments about the puzzle implementation to collect the required data. The writer concludes that the teachers should give a game in their teaching learning process, especially puzzle. Although, the game is monotonous, but at least it can influence the student's motivation in their study. The student can be more active and this game encourages them to compete each other. The result of the research is that puzzle game is an effective method to teach and motivate the young children in mastering vocabulary skill.